New enhanced strain elements for incompressible problems - J. M. A. César (1999)
A new enhanced strain element, based on the definition of extra compatibles modes of deformation added to the standard four-node finite element, is initially presented. The element is built with the objective of addressing incompressible problems and avoiding locking effects. By analysing at the element level the deformation modes which form a basis for the incompressible subspace the extra modes of deformation are proposed in order to provide the maximum possible dimension to that subspace. Subsequently another new element with more degrees of freedom is formulated using a mixed method. This is done by including an extra field of variables related to the derivatives of the displacement field of the extra compatible modes defined previously. The performance of the elements proposed is assessed in linear and non-linear situations. Copyright (C) 1999 John Wiley & Sons, Ltd.